The United States Singapore Free Trade Agreement : highlights and insights - Koh, Tommy T. B. (Tommy Thong Bee), 1937-; Chang, Li Lin (World Scientific Pub ; Institute of Policy Studies, 2004)
On 1 January 2004, the USSingapore Free Trade Agreement (USSFTA)came into force. The USSFTA was the result of a two-year negotiationprocess which started towards the end of the Clinton Administrationand concluded under the Bush Administration. How did the negotiationprocess straddle the two administrations? What is the rationale forthe FTA? What were the unique features of the negotiating process? Wasnegotiating with the US different from negotiating with othercountries? How will the FTA benefit the two countries? What is theimpact on ASEAN, APEC and the WTO?This book captures some of the per.